The Main Challenges of Gender Based International Labor Mobility: Transnational Migrant Families from Georgia - Ia Iashvili; Giorgi Gogsadze; Tinatin Gvenetadze (Journal of Eurasian Studies)
The goal of the paper is to shed light on gendered nature of labor migration in the post-Soviet Georgian transitional families. Based on qualitative research methods, this study tries to identify how both, an immigrant wife and her husband left in Georgia conceptualize their gender roles and functions toward family members amid existing challenges. Our research showed that the both financial and emotional burdens of the family are on the part of immigrant women mainly. In few families, fathers take care of children, but in most cases mother’s role is played by a grandmother. Even though almost all respondents noted improvement of economic conditions, the temporary separation of the family members is seen as a social loss. The vast majority of families have not invested remittances in small businesses. It indicates the stagnation of the process of economic and social development in Georgia that restricts the migrants’ way back to home.